Investment Manager's Ability and Characteristics of Mutual Funds as Determinants of Sharia Stock Mutual Fund Performance in Indonesia - Halim Pandu Latifah; Eko Hariyanto; Erny Rachmawati; Bima Cinintya Pratama (Eduvest - Journal of Universal Studies, 2026)
As a country with the largest Muslim-majority population worldwide, Indonesia is the most promising market for Islamic-based products. This study examines the effects of fund manager skills and fund characteristics on Islamic mutual fund performance in Indonesia. Quantitative analysis tested stock selection skill, market timing ability, expense ratio, fund age, and fund size using multiple linear regression on panel data (2018–2022) from 13 purposively sampled funds (65 observations), analyzed with EViews 12. Data sourced from fund reports, Bank Indonesia (BI), and OJK. The Treynor-Mazuy model measured manager abilities; Sharpe ratio assessed performance. Results show stock selection skill (coeff. = 1.198, p = 0.0005) and expense ratio (coeff. = 4.618, p = 0.0905) significantly positively affect performance, with stock selection having the strongest impact. Market timing (p = 0.6861), fund age (p = 0.2336), and size (p = 0.4920) are insignificant. Adjusted R-squared (0.178621) explains 17.8% of variation. Findings urge prioritizing stock selection and research over market timing or size expansion.